A proposed guidance program for the Ateneo de Naga, City of Naga - Llorin, Sofronio F. (Animo Repository, 1973)
v. 1. This study proposes a centralized guidance program for Ateneo de Naga, which consists of a college department and a high school department. The research methods utilized in this study were the descriptive and the deliberative methods. The basis for proposing a centralized guidance program for the Ateneo de Naga was the survey on problems confronting the students, which was conducted in the high school department during the second semester of schoolyear 1971-72. Out of 870 boys, 798 participated in the survey. No problem survey was conducted in the college department. The instrument, called the Ateneo de Naga Problem Survey and Checklist, was developed by a committee composed of the college student counselor, the high school guidance coordinator, and the high school guidance counselor. Other tools and techniques, like actual observations of both departments at the Ateneo de Naga and dialogues with student groups and professional workers in the school, were used to obtain more facts and data. The problem survey conducted revealed the following problem areas according to order of significance : studies, personal concern, social concern, vocational and educational planning, social adjustment, school adjustment, finances, health, and religion. These strongly indicated that the existing guidance services have not adequately met the needs of the students. Furthermore, through observations, interviews, and dialogues with students and professional workers, it was found that the same problem areas, although in a different order of significance, also existed in the college department. Recognizing the common needs of the students of the Ateneo de Naga, knowing the deficiencies of the existing guidance services, and taking into account the human and financial resources available, a centralized guidance program was proposed for the school. It was recommended that approval be sought for an organizational revamp in the present set-up of the Ateneo de Naga. It was also suggested that an on-going in-service training for t v. 2. This study aims to analyze the items of the preliminary version of an achievement test in mathematics which was administered to a group of elementary school graduates. The subjects of the study were 329 high school freshmen of the Ateneo de Naga and Colegio de Sta. Isabel who took the test during the early part of the school year 1971-72. Designed to measure the amount of learning acquired by graduates of elementary schools in mathematics, an achievement test was constructed by a committee of high school mathematics teachers which consisted of 110 multiple-choice items. The high-low-27- per cent method of item analysis was conducted on the test and an overall evaluation of each test item was performed on the basis of three tentative criteria, namely : difficulty level, discrimination level, and option analysis. Based on the findings of the study, it was concluded that 70 items or 64 percent of the test items, which were those appraised as good and fair, were to be included in the final form of the test. Twenty (20) items or 18 percent of the items were to be revised or improved before deciding to include these in the final form. Twenty (20) items or 18 percent were to be discarded inasmuch as these discriminated very poorly between the high-achieving students and the low-achieving ones. The preliminary version of this achievement test was, in general, fairly difficult to this particular group of students tested. In the light of the findings in this study, it was recommended that the final form of the test should be composed of seventy items considered as good and fair items. The items in the final form should be arranged from the least to the most difficult using the delta values. The final form should be administered to a representative sample for the purpose of establishing local norms. v. 3. The subject of this case study is Joselito Hernandez, an 18 year old college freshman in one of the prominent Catholic colleges of Manila. Joselito who belongs to an upper-middle class family from the south, lives for the first time in a boarding house for boys. Separated from his ten elder brothers and sisters who are all married, and away from his domineering mother, Joselito is confronted with interpersonal problems as he begins to adjust to his new environment and to his new school. Joselito referred himself to the counselor when he was faced with a problem of relating with a group of homosexuals. Other sessions revealed that aside from the initial difficulty he was confronted with, he had adjustment problems with his board mates, his study skills and habits were inadequate and his concentration was weak. He spoke of his difficulty relating to some members of his family. Joselito also expressed his lack of confidence in himself, a characteristic, which to him was caused by the over-protection of his parents, especially his mother. He accepted that because of this, he tended to be lazy and dependent. In high school, his interests and activities revolved mostly in the field of athletics. Although he did not make good in academics, he felt that he could do better if only he pushed himself to achieve more. He felt that a deeper knowledge of himself and his capacities would lead to self-acceptance. The counselee found his inability to concentrate and his poor study habits as pressing problems because of the probability of failure in any of his subjects, an eventuality he was anxious about. This anxiety was caused by a condition imposed on him by his mother that failure in any of his subjects would mean that he would be recalled to his home province and study in one of the local colleges there. Initially, information and data regarding the counselee were gathered from four sources : 1) twenty-three (23) interviews with the counselee conducted within a period from July, 1972 to April , 1973 2) two (2) inter